Reverse Genetics of Mononegavirales: The Rabies Virus Paradigm - Conzelmann, Karl-Klaus (Sendai Virus Vector, 2013)
The neurotropic rabies virus (RABV) is a prototype member of the Mononegavirales order of viruses and is the most significant human pathogen of the Rhabdoviridae family. A reverse genetics system for RABV was established almost 20 years ago, providing a paradigm for other Mononegavirales members as well. The availability of engineered recombinant viruses opened a new era to study common aspects of Mononegavirales biology and specific aspects of the unique lifestyle and pathogenesis of individual members. Above all, the knowledge gained has allowed engineering of beneficial biomedical tools such as viral vectors, vaccines, and tracers. In this chapter, the development of the classical rabies virus reverse genetics approach is described, and some of the most exciting biomedical applications for recombinant RABV and other Mononegavirales are briefly addressed.